The use of emerging technologies for authentic learning: A South African study in higher education. (4th June 2013) - Bozalek, Vivienne; Gachago, Daniela; Alexander, Lucy; Watters, Kathy; Wood, Denise; Ivala, Eunice; Herrington, Jan
Abstract It is now widely accepted that the transmission of disciplinary knowledge is insufficient to prepare students leaving higher education for the workplace. Authentic learning has been suggested as a way to bring the necessary complexity into learning to deal with challenges in professional practice after graduation. This study investigates how South African higher educators have used emerging technologies to achieve the characteristics of authentic learning. A survey was administered to a population of 265 higher educators in South Africa who self‐identified as engaging with emerging technologies. From this survey, a sample of 21 respondents were selected to further investigate their practice through in‐depth interviewing using Herrington, Reeves and Oliver's nine characteristics of authentic learning as a framework. Interrater analysis undertaken by five members of the research team revealed both consistencies and differences among the twenty one cases across the nine elements of authentic learning. The highest levels of authenticity were found for the elements authentic context and task, and the lowest for articulation. Furthermore, there was a moderate correlation identified between levels of authenticity and the role played by emerging technologies in achieving the authenticity, showing a potentially symbiotic relationship between them.